The effect of ISO 9000 registration on company profitability in Malaysia / Nurul Inna Adian (Faculty of Business and Management, 2007)
Registration to the ISO 9000 standard have grown rapidly in worldwide. This suggests that there is a widespread belief in the business benefits of ISO 9000 accreditation. By achieving the ISO certification, people assumed that the company able to meet the best quality for their businesses. Financially, do ISO 9000 registration gives benefits through the company profitability? The objective of this study is to assess the effect of before and after ISO 9000 implementation on firm profitability of manufacturing listed companies in Malaysia. This study will use 40 samples, which are from manufacturing sector, that listed on Bursa Malaysia. The time horizon is period 3 years before and 3 years after obtaining the ISO 9000 certification. The samples came from 2 categories: main boarder and second boarder by using 3 variables of company profitability measurements: net profit margin (NPM), return on assets (ROA) and return on equity (ROE) in order to examine the effect of ISO 9000 implementation on companies profitability. Paired sample t-test using SPSS software will be used to compare between profitability before and after implementation of ISO 9000. The researcher found that, the firms which successfully implemented ISO 9000 do show any significant increase in company profitability for main boarder companies. For second boarder companies, the firms which successfully implemented ISO 9000 do show insignificant only through ROA. Other variables has show significant when the firms managed to increase their profitability.